Wykaż, że jeśli a>b>0, to 2(b²- |ab|) + |b-a| × |a+b| > 0.​

Odpowiedź :

Jeżeli [tex]a>b>0[/tex], to:

[tex]ab>0 \Rightarrow |ab|=ab[/tex]

[tex]b-a<0\Rightarrow |b-a|=-b+a[/tex]

[tex]a+b>0 \Rightarrow |a+b|=a+b[/tex]

Zatem [tex]2(b^2-|ab|)+|b-a|\cdot |a+b|>0 \Leftrightarrow 2(b^2-ab)+(-b+a)\cdot (a+b)>0[/tex]

[tex]2(b^2-ab)+(-b+a)\cdot (a+b)>0\\2b^2-2ab-ab-b^2+a^2+ab>0\\a^2-2ab+b^2>0\\(a-b)^2>0\\[/tex]

Co jest oczywiście spełnione dla dowolnych liczb rzeczywistych spełniających nierówność [tex]a>b>0[/tex].